Decision making within international organizations - Reinalda, Bob; Verbeek, Bertjan, 1960- (Routledge/ECPR studies in European political science, 2004)
"International organizations are increasingly important in the era of globalization but little is known about decision making within these institutions. This edited volume investigates how much influence governments as well as non-state actors, such as non-governmental organizations and international bureaucracies, have upon decision making and the specific ways in which they try to affect international outcomes."--Jacket